Study on adsorptive capability of acid activated charcoal for desulphurization of model and commercial fuel oil samples - Shah, Syed Sikandar [UNESP]; Ahmad, Imtiaz; Ahmad, Waqas; Ishaq, Muhammad; Gul, Kashif; Khan, Razia; Khan, Hizbullah (Elsevier, 2018)
The present study was planned to explore the selective desulphurization efficiency of the acid-modified activated charcoal (AC) as an adsorbent. The oil samples selected were the model oil and the commercial kerosene & diesel. The adsorption capacity of the AC was evaluated for the removal of one of the sulfur analogs i.e. dibenzothiophene (DBT) present in the fuel samples under a set of experimental conditions. The kinetics and thermodynamics of the DBT desulphurization were studied. It was observed that the adsorption firmly followed pseudo-second order kinetic model. Moreover, the experimental value of the amount of DBT adsorbed at equilibrium qe was nearly equal to the value calculated from the pseudo-second order kinetic model. Langmuir and Freundlich adsorption isotherm models were applied and the experimental data best fitted with the Langmuir and Freundlich adsorption isotherm models. Compared to other commercially available adsorbents, the acid-modified AC was found to be cost-effective, highly efficient and selective for the DBT removal from the model as well as real petroleum based oils.
Keywords: Desulphurization; Environment; Model oil; Petroleum; Regeneration